Diabetic Retinopathy: A Literature Review - Maulida, Rizka Ayu; Afifah, Fiza (Jurnal Biologi Tropis, 2024)
Diabetic retinopathy is a complication of diabetes mellitus characterized by visual impairment and potentially blindness. This literature review aims to enhance knowledge about diabetic retinopathy. Sources for this review were gathered through online databases and include review articles, research studies, and professional guidebooks related to the topic. Hyperglycemic conditions associated with diabetes mellitus trigger angiogenesis and inflammatory pathways, leading to diabetic retinopathy. The condition is classified into two types: non-proliferative diabetic retinopathy and proliferative diabetic retinopathy, with management strategies varying depending on the type. As the prevalence of diabetes mellitus increases, so does the expected incidence of diabetic retinopathy, highlighting the need for effective prevention strategies, which include both primary and secondary prevention.